Women and men farmer perceptions of economic and health benefits of orange fleshed sweet potato (OFSP) in Phalombe and Chikwawa districts in Malawi - Mudege, Netsayi N.; Mayanja, S.; Muzhingi, T. (Springer, 2017)
Based on a qualitative study conducted in Chikwawa and Phalombe in Malawi, this paper looks at farmers perceived economic, health and social benefits of production, commercialization and consumption of orange fleshed sweet potato (OFSP). Findings demonstrate that perceived health and economic benefits were key determinants in adoption of OFSP varieties. Men and women are receptive to health and nutrition based promotion messages. Health benefits included increased energy to work, for sex, improved health, general wellbeing and cognitive development for children. Economic benefits included ability to invest income from selling of OFSP roots and vines in housing, purchase of livestock, food, and land. Income from OFSP enabled farmers to diversify into other cash crops. Women also mentioned increasing self-esteem due to increased incomes since they no longer needed to ask for money from their husbands to buy household consumables. However, men and women did not have equal access to and control of economic benefits and therefore women could not invest in large assets like cattle, land and agriculture equipment which could contribute to food security and are important to moving out of poverty. Interventions to increase farmer incomes should be designed in ways that allow women to actively participate and benefit. Since livestock are a key investment option and also contribute to food security and diversification, options for making sweet potato based silage for animal feed would be an important intervention especially for vines that would otherwise go to waste due to lack of markets.